Tindak Pidana Korupsi dan Sanksi Pidana Mati Perspektif Keadilan Hukum - Amirullah, Amirullah (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2013)
Corruption is included as a crime which expands into a transnational crime, destroying the moral values of the nation, hampering and harming the development of the nation, a creation of a closed path of justice, prosperity and welfare of the Indonesian people. Death penalty is an option of criminal sanctions applied in the legal system in Indonesia. The death penalty attached and integrated in the legal system in Indonesia which was formerly influenced by the complexity of its background. At the philosophical level it shows that all legislations related to the formulation of corruption and death penalty have the background of moral values based on Pancasila as a philosophical footing. The death penalty of corruption in Indonesia within the perspective of a legal justice, contained in the formulation of Law No. 20 year 2001 about the Amendment of Law No. 31 year 1999 about eradication to corruption, chapter II, article 2, paragraph (2), shows a part of the positive law. The image of the positive law in Indonesia recognizes the existence of natural law. It is reflected in the philosophical values of the nation, Pancasila (believe in one God). Consequently, the products of the positive law in Indonesia must be derived from the natural law, and the natural law is derived from the eternal law (divine law).